Entrepreneurial Intentions of Undergraduate Management Students in Nepal: A Behavioral Perspective - Gautam, Prakat; Adhikari, Khem; Thapa, Pawan (DAV Research Journal, 2026)
The purpose of the paper was to assess the influence of need for achievement, risk propensity and attitude towards entrepreneurship on the entrepreneurial intention of undergraduate management students. The study employed a descriptive and causal research design, utilizing a primary dataset collected from 97 management students via structured survey questionnaires. Data were analyzed using descriptive statistics, correlation and multiple regression analysis to test the hypothesized relationships between the variables, while the reliability of the measurement scales was confirmed through Cronbach’s Alpha. The analysis revealed that Need for Achievement and Risk Propensity are significant predictors of entrepreneurial intention. However, while students reported a generally positive attitude towards entrepreneurship, this factor did not have a statistically significant influence on their actual intention to start a business. Need for achievement and risk propensity were found to be significant predictors of entrepreneurial intention, while attitude toward entrepreneurship did not show a significant relationship. Universities should offer personalized support, such as mentorship and hands-on learning to nurture entrepreneurial interest across all students. Recognizing that entrepreneurial potential isn’t limited by gender or course, business schools must create inclusive environments.